1971 California Democratic State Central Committee Luncheon (1971)
This program outlines the 1971 California Democratic State Central Committee Convention Luncheon, held January 23–24 in Sacramento. The luncheon featured an invocation, recognition of guests, introductions by legislative leaders, and an address by U.S. Senator Edmund Muskie, with Senator Alan Cranston introduced as a featured speaker. The booklet also lists members of the Special Events Committee, party officers, and convention officers overseeing the event.